The Concept of Sadd Al-Dzāri‘Ah from the Perspective of Asy-Syāṭibī and Al-Qarāfī Towards Minimum Marriage Age Policy in Indonesia - Amrullah Hayatudin; Muhammad Tegar Syaekhudin (Asy-Syari'ah, 2025)
The amendment of Indonesian Marriage Law No. 16 of 2019 which raises the minimum marriage age to 19 for both men and women is a crucial step by the government to reduce the prevalence of child marriage and the wide-ranging impacts on reproductive health, education, and social welfare. From the perspective of Islamic law, this policy reflects the principle of Sadd al-Dzāri‘ah which is a preventive legal method aimed at blocking any avenue leading to harm (mafsadah). Therefore, this study aimed to analyze the application of Sadd al-Dzāri‘ah as conceptualized by Imam Asy-Syāṭibī and Al-Qarāfī using a library analysis and a normative juridical method. The results showed that revising the minimum marriage age supported the preventive essence of Sadd al-Dzāri‘ah, as it mitigated negative consequences including psychological immaturity, maternal health risks, and socioeconomic inequality. Therefore, this policy embodied the legal protection for society and also actualized the objectives of Islamic law (maqāṣid asy-syarī‘ah) in preserving life (ḥifẓ an-nafs), intellect (ḥifẓ al-‘aql), and lineage (ḥifẓ an-nasl), reaffirming the relevance of fiqh (Islamic jurisprudence) in addressing contemporary legal and social issues.